2015
DOI: 10.1161/strokeaha.115.009843
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Anemia and Cerebral Venous Thrombosis

Abstract: Background and Purpose— Anemia is often considered to be a risk factor for cerebral venous thrombosis (CVT), but this assumption is mostly based on case reports. We investigated the association between anemia and CVT in a controlled study. Methods— Unmatched case–control study: cases were adult patients with CVT included in a single-center, prospective database between July 2006 and December 2014. Controls were subjects from the control population of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…19,20 Moreover, iron deficiency anemia has been associated with risk of incident VTE, 21 VTE recurrence, 22 PE, 23 and cerebral venous thrombosis. 24 However, iron deficiency anemia may have several causes, which may act as confounders for the association between iron deficiency and VTE. 25 Therefore, whereas the association between iron deficiency and high RDW as well as the association between high RDW and VTE risk seems well established, the association between iron deficiency and VTE remains to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Moreover, iron deficiency anemia has been associated with risk of incident VTE, 21 VTE recurrence, 22 PE, 23 and cerebral venous thrombosis. 24 However, iron deficiency anemia may have several causes, which may act as confounders for the association between iron deficiency and VTE. 25 Therefore, whereas the association between iron deficiency and high RDW as well as the association between high RDW and VTE risk seems well established, the association between iron deficiency and VTE remains to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a strong association between RDW and iron deficiency anemia . Moreover, iron deficiency has recently been associated with increased risk of VTE recurrence, and anemia might be associated with risk of cerebral venous thrombosis . However, a recent case‐control study found no association between anemia and pulmonary embolism .…”
Section: Discussionmentioning
confidence: 95%
“…24,38 Moreover, iron deficiency has recently been associated with increased risk of VTE recurrence, 39 and anemia might be associated with risk of cerebral venous thrombosis. 40 However, a recent case-control study found no association between anemia and pulmonary embolism. 41 Moreover, the proportion of women with anemia was reported to be considerably higher in those of premenopausal age than in those of postmenopausal age in our cohort.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, an association between anemia and cerebral venous thrombosis was reported [49]. Therefore, anemia patients should be monitored carefully.…”
Section: Discussionmentioning
confidence: 99%